EWaS3 2018 2018
DOI: 10.3390/proceedings2110646
|View full text |Cite
|
Sign up to set email alerts
|

Sulphide Biooxidation in Activated Sludge Diffusion Process: Microbiological and Biochemical Effects

Abstract: Sulphide was adopted as odorous compound in a simulation of AS Diffusion, an interesting process to treat odors at wastewater treatment plants by diffusing odorous air into aerobic basins. Its behaviour were experimentally evaluated along with its effects on the biomass and the biological processes supposed by some author in an AS diffusion test. Two bench scale sequencing batch reactors (SBRs) were fed in parallel on real primary sewage and monitored after adding increasing concentrations of sulphide to one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Instead of desorbing the dissolved gases into a waste gas, some technologies consider D-H 2 S or D-CH 4 direct biological oxidation in the bulk liquid, thus removing the requirement for further treatment of a waste gas. Activated sludge has been suggested for D-CH 4 (Daelman et al 2012) and D-H 2 S (Blonda et al 2018) biological oxidation, and removal efficiencies of 80% and 94% have been reported.…”
Section: Oxidation Of D-ch 4 and D-h 2 S In Biological Reactorsmentioning
confidence: 99%
“…Instead of desorbing the dissolved gases into a waste gas, some technologies consider D-H 2 S or D-CH 4 direct biological oxidation in the bulk liquid, thus removing the requirement for further treatment of a waste gas. Activated sludge has been suggested for D-CH 4 (Daelman et al 2012) and D-H 2 S (Blonda et al 2018) biological oxidation, and removal efficiencies of 80% and 94% have been reported.…”
Section: Oxidation Of D-ch 4 and D-h 2 S In Biological Reactorsmentioning
confidence: 99%